Anteseden Senjangan Anggaran Desa Di Kabupaten Kebumen - Dian Pertiwi; Arya Samudra Mahardhika (Faculty of Economics and Business Universitas Muhammadiyah Riau, 2019)
This study aims to examine the effect of budgetary participation, individual capacity, and clarity of budget targets on village budgetary slack in Kebumen District. Respondents in this study are village officials involved in budgeting. The sample in this study was 42 respondents. Data obtained from the distribution of questionnaires directly to respondents. The research hypothesis was tested by multiple regression analysis. The results of this study indicate that; (1) budgetary participation has a positive and significant effect on budgetary slack, (2) individual capacity has no effect on budgetary slack, (3) clarity of budgetary objectives has a positive and significant effect on budgetary slack